Reading Sartre - Catalano, Joseph S. (Cambridge : Cambridge University Press, 2010)
In this volume, Joseph Catalano offers an in-depth exploration of Jean-Paul Sartre's four major philosophical writings: Being and Nothingness, Saint Genet: Actor and Martyr, The Critique of Dialectical Reason, and The Family Idiot. These works have been immensely influential, but they are long and difficult and thus challenging for both students and scholars. Catalano here demonstrates the interrelation of these four works, their internal logic, and how they provide insights into important but overlooked aspects of Sartre's thought, such as the body, childhood, and evil. The book begins with Sartre's final work, The Family Idiot, and systematically works backward to Being and Nothingness. Catalano then repeats the study by advancing chronologically, beginning with Being and Nothingness and ending with The Family Idiot and an afterword on Flaubert's Madame Bovary. Readers will appreciate Catalano's subtle readings as well as the new insights that he brings to Sartre's oeuvre.
Title from publisher's bibliographic system (viewed on 09 Oct 2015).